Linear Seesaw in A5′ Modular Symmetry With Leptogenesis - Behera, Mitesh Kumar; Mohanta, Rukmani (Frontiers in Physics, 2022)
In this paper, we investigate the implication of modular Γ^′_5 A^′_5 symmetry on neutrino oscillation phenomenology in the linear seesaw framework. In order to achieve the well defined mass structure for the light active neutrinos as dictated by the linear seesaw mechanism, we introduce six heavy fermion fields along with a pair of weightons to retain the holomorphic nature of the superpotential. The notable feature of modular symmetry is that, it reduces the usage of flavon fields significantly. In addition, the Yukawa couplings transform non-trivially under the flavor symmetry group and expressed in terms of the Dedekind eta functions, the q expansion of which renders numerical simplicity in calculations. We demonstrate that the model framework diligently accommodates all the neutrino oscillation data. Alongside, we also investigate the effect of CP asymmetry generated from the decay of lightest heavy fermions to explain the observed baryon asymmetry through the phenomenon of leptogenesis.